Cyclic bond behaviors between corroded steel bar and concrete under the coupling effects of hoop FRP confinement and sustained loading. (15th September 2019) - Zhou, Yingwu; Zheng, Bowen; Zhao, Debo; Dang, Leijun; Sui, Lili; Li, Dawang; Xing, Feng
Abstract: The dual action of hoop confinement and sustained loading significantly affects the cyclic bond performance between the corroded steel bar and the concrete. This process has been recognized, but the cyclic bond performance has not been well defined. This paper defines and analyzes this process through research involving the fabrication of 30 steel bar-concrete bond specimens. The corrosion of these steel bars was accelerated with and without sustained loading, after which the specimens were subjected to cyclic loading. This investigation covers the corrosion rate, sustained load, and hoop confinement provided by carbon fiber reinforced polymer (CFRP) laminate strips (used to wrap columns), which are referred to herein as CFRP confinement. Attention is also paid to the thickness changes of the concrete cover and its effect on bond strength. The results show that an appropriate degree of corrosion can improve both the static and cyclic bond performance; sustained load was beneficial to the cyclic behavior of the corroded interface in case of existing hoop confinement but detrimental to it if no hoop confinement was applied, indicating that the hoop confinement was of great importance to eliminating the negative influence of the sustained load on the bond performance of the corroded interface. The existence of the hoop confinement significantly improved the hysteretic behavior and the energy dissipation of the interface. The research results provided an experimental basis for the cyclic performance evaluation of structural reinforcement of corroded reinforced concrete structures under the coupling effects of hoop confinement and sustained loading.